2008
DOI: 10.1051/0004-6361:200809710
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of the centrifugally induced curvature drift instability in AGN winds

Abstract: Aims. We investigate the centrifugally driven curvature drift instability to study how field lines twist close to the light cylinder surface of an AGN, through which the free motion of AGN winds can be monitored. Methods. By studying the dynamics of the relativistic MHD flow close to the light cylinder surface, we derive and solve analytically the dispersion relation of the instability by applying a single particle approach based on the centrifugal acceleration. Results. Considering the typical values of AGN w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 15 publications
0
16
0
Order By: Relevance
“…However, rotation and relativity are hard to match with each other [4] because of some puzzling features. In astrophysics, there exists the so-called light cylinder problem, the lack of understanding about what happens in the region where the magnetic field lines of a rigidly rotating pulsar reach the speed of light [4][5][6]; some authors argue that the magnetic field lines rotate with a speed greater than that of the light beyond this cylinder [7]. The electromagnetic fields have also opened fundamental questions in terms of rotational motion [8,9], and this theory provides a strong support to model several astrophysical objects, such as pulsars [10,11] and active galactic nuclei [12].…”
Section: Introductionmentioning
confidence: 99%
“…However, rotation and relativity are hard to match with each other [4] because of some puzzling features. In astrophysics, there exists the so-called light cylinder problem, the lack of understanding about what happens in the region where the magnetic field lines of a rigidly rotating pulsar reach the speed of light [4][5][6]; some authors argue that the magnetic field lines rotate with a speed greater than that of the light beyond this cylinder [7]. The electromagnetic fields have also opened fundamental questions in terms of rotational motion [8,9], and this theory provides a strong support to model several astrophysical objects, such as pulsars [10,11] and active galactic nuclei [12].…”
Section: Introductionmentioning
confidence: 99%
“…The corresponding mechanism of reconstruction of magnetospheres in the LC area has been studied for pulsars and supermassive black holes (Ref. 13) and it has been shown that under certain circumstances the field lines obtain the configuration of the Archimede's spiral.…”
Section: Introductionmentioning
confidence: 99%
“…The similar problem, thus excitation of the CDI in AGN magnetospheres was studied in Ref. 12 and it has been shown that the instability is very efficient and might strongly influence processes in AGN plasmas. The major restriction of this work was that we have studied particles with exactly equal initial phases, and it is clear that most of the electrons have different values of phases.…”
Section: Light Cylindermentioning
confidence: 94%
“…On the other hand, in Ref. 12 it has been shown that AGN magnetospheric parameters satisfy the condition ω 0 /Ω ≪ 1. This in turn means that all terms with Ω(2s + q) and Ω(2[s + µ] + q) (2s + q = 0, 2[s + µ] + q = 0) are rapidly oscillating and do not influence the final result.…”
Section: Excitation Of Curvature Drift Wavesmentioning
confidence: 99%